ANALISIS KESEPAKATAN KERJA SAMA INDONESIA-VIETNAM TERKAIT PERBATASAN WILAYAH PERAIRAN DI LAUT CHINA SELATAN - Dwi Panorama, Anggun; Nurfitria, Marshanda (Jurnal Ilmiah Hubungan Internasional Fajar, 2023)
Indonesia and Vietnam are both quite often heated because of the amount of illegal fishing by Vietnam in Indonesian waters. The lack of clarity on the territorial waters of the two countries has made their relationship a little heated even though they have previously signed a ratified agreement. This analysis aims to find out the real reason that Indonesia wants from its agreement with Vietnam. Judging from the existing data, it is true that Vietnam still often carries out illegal activities in Indonesian waters. This research uses analytical qualitative methods by looking at the driving and inhibiting factors, impacts and objectives of cooperation between Indonesia and Vietnam as well as what problems in the South China Sea border area are faced by Indonesia and Vietnam. Based on existing data, the results of the research clearly show that Vietnam still commits a lot of illegal actions every year and the bilateral meeting between Indonesia and Vietnam in 2022 is the reason for Indonesia to return to overcome this transnational crime problem.